Directly Coupled Versus Spectator Linkers on Diimine PtII Acetylides—Change the Structure, Keep the Function?. Issue 72 (30th November 2017) - Archer, Stuart A.; Keane, Theo; Delor, Milan; Bevon, Elizabeth; Auty, Alexander J.; Chekulaev, Dimitri; Sazanovich, Igor V.; Towrie, Michael; Meijer, Anthony J. H. M.; Weinstein, Julia A.
Abstract: Modification of light‐harvesting units with anchoring groups for surface attachment often compromises light‐harnessing properties. Herein, a series of [donor–acceptor–anchor] platinum(II) diimine (bis‐)acetylides was developed in order to systematically compare the effect of conjugated versus electronically decoupled modes of attachment of protected anchoring groups on the photophysical properties of light‐harvesting units. The first examples of "decoupled" phosphonate diimine Pt II complexes are reported, and their properties are compared and contrasted to those of carboxylate analogues studied by a diversity of methods. Ultrafast time‐resolved IR and transient absorption spectroscopy revealed that all complexes have a charge‐transfer (CT) lowest excited state with lifetimes between 2 and 14 ns. Vibrational signatures and dynamics of CT states were identified; the assignment of electronic states and their vibrational origin was aided by TDDFT calculations. Ultrafast energy redistribution accompanied by structural changes was directly captured in the CT states. A significant difference between the structures of the electronic ground and CT excited states, as well as differences in the structural reorganisation in the complexes bearing directly attached or electronically decoupled anchoring groups, was discovered. This work demonstrates that decoupling of the anchoring group from the light‐harvesting core by a saturated spacer is an easy approach to combine surface attachment with high reduction potential and ten times longer lifetime of the CT excited state of the light‐absorbing unit, and retain electron‐transfer photoreactivity essential for light‐harvesting applications. Abstract : Direct versus conjugated attachment of electron‐withdrawing substituents on Pt II diimine acetylide complexes was studied by ultrafast time‐resolved IR and transient absorption spectroscopy to examine the effect of decoupling the electron‐withdrawing groups on the excited state (see figure).